Data on Gabonese rodents and their Plasmodium - Boundenga, Larson (Data Brief, 2019)
In this paper present data on the description of rodent species living around human dwelling in some villages of Gabon and their malaria parasites. Rodents are known to colonize various environments, such as forest; domestic or peridomestic environment. They are known to be the hosts of many parasites. Data presented here the circulation of malaria parasites in Gabonese rodents was shown; the estimation of pairwise genetic distances (p-distance) between rodents malaria parasites. We also provide data on rodent species diversity in Gabon. Three hundred and forty-five samples from rodents conserved in biobank of International Center of Medical Researches of Franceville (CIRMF) were used for the study. These samples were collected in six villages of southeastern of Gabon between 2009 and 2016 for routine monitoring of infectious disease. Such data can be used to describe and understanding the evolution and systematics of malaria parasite. This data set support the main findings presented in the research article [1].